IMPLEMENTASI AKAD MUKHABARAH PADA PERTANIAN PADI - Moch. Zaenal Azis Muctharom (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This research aims to determine the implementation of mukhabarah contracts in lowland rice farming businesses in Sokogrenjeng Village, using qualitative methods with a field research approach. The subjects are land owners and cultivators in Sokogrenjeng Village, and the object is the practice of mukhabarah for agricultural products among the farming community of Sokogrenjeng Village. Data collection techniques include observation, interviews and documentation. The results of this research provide an overview of the background to mukhabarah cooperation between land owners and sharecroppers in Sokogrenjeng Village, highlighting the existence of cooperation between parties who do not have their own agricultural land and parties who do not have the ability and time to manage their land. The practice of mukhabarah in rice farming in Sokogrenjeng Village involves land owners handing over their land to sharecroppers, who then manage the land. After harvest, both parties have the right to receive the harvest from the rice fields according to the agreement made in the implementation of daily profit sharing using the mukhabarah system in Sokogrenjeng Village